Potential of Bacillus thuringiensis isolates to manage Gonipterus platensis (Coleoptera: Curculionidae) larvae populations - Jordan, Carolina [UNESP]; De Carvalho, Vanessa Rafaela [UNESP]; Horta, André Ballerini [UNESP]; Lemos, Manoel Victor Franco [UNESP]; Barbosa Rodrigues, Jardel Diego [UNESP]; De Souza Passos, José Raimundo [UNESP]; Domingues, Maurício Magalhães [UNESP]; Zanuncio, José Cola; Wilcken, Carlos Frederico [UNESP] (Oxford University Press (OUP), 2025)
The growing expansion of eucalyptus plantations in Brazil and the impact of exotic pests, such as Gonipterus platensis, demand effective, and sustainable biological control strategies. The aim of this study was to assess the pathogenicity of 10 Bacillus thuringiensis (Bt) isolates to neonate Gonipterus platensis larvae, commonly known as the eucalyptus weevil (Coleoptera: Curculionidae) with the specific focus of evaluating their potential to manage this pest while preserving its egg parasitoid, Anaphes nitens. To achieve this, the genomic DNA of the 10 Bt isolates was extracted using the thermal lysis method for molecular characterization of their Cry and Vip proteins. Neonate G. platensis larvae were subjected to bioassays with each isolate, at a concentration of 1 × 109 spores/ml, was applied on 10 larvae per replication (3 replications). The concentration and lethal time to kill 50% of the larvae were determined for the most effective isolates. The Bt isolates 107 and 178 isolates even at concentrations 10× lower than those recommended for commercial Bacillus thuringiensis var. tenebrionis (Btt) formulations against Coleoptera pests, achieved 100% mortality of G. platensis larvae. These isolates, with coleopteran-specific genes, caused high mortality of neonate Gonipterus platensis larvae. This indicates their potential for the biological control of this pest and maybe of other Coleoptera pests. Their use poses minimal risk to non-target organisms such as the egg parasitoid A. nitens and indicates a promising avenue for integrated pest management strategies with effective pest control while preserving the ecological balance.
Keywords: biological control; entomopathogenic bacteria; pathogenicity; transgenics